MiR-142-3p targeting NUCKS1 inhibits proliferation and invasion of pancreatic cancer cells. Issue 1 (1st January 2020) - Zhu, Kexiang; Zhang, Zhengcong; Zhang, Hui; Wang, Zhengfeng; Wang, Fanghong
Abstract: Objective: To investigate the effects of microRNA-142-3p (miR-142-3p) on the biological characteristics of pancreatic cancer cells and its mechanism. Methods: The expression of miR-142-3p and nuclear casein kinase and cyclin-dependent kinase substrate 1 (NUCKS1) in pancreatic tissues and four cancer cell lines (Panc-1, BxPC-3, AsPC-1, MIA-PaCa2) were detected by Quantitative PCR (qPCR) or Western blot. The cell viability of pancreatic cancer cells was examined by MTT assay. The apoptosis of pancreatic cancer cells was measured by flow cytometry. Transwell assay was utilized to test the migration and invasion of pancreatic cancer cells. Bioinformatics analysis for miR-142-3p was conducted and the dual luciferase reporter gene assay was utilized to further validate the predicted target relationship. The protein levels of PI3K, p-AKT and T-AKT were analyzed by Western blot. Results: The expression of miR-142-3p was down-regulated, while the expression of NUCKS1 was significantly up-regulated in pancreatic tissues and four cancer cell lines. The expression of miR-142-3p in pancreatic tissues was inversely correlated with NUCKS1 expression. Overexpression of miR-142-3p inhibited the cell viability, cell migration, and invasion, while promoted cell apoptosis of AsPC-1 and MIA-PaCa2 cells. MiR-142-3p targeted NUCKS1 and negatively regulated NUCKS1. Overexpression of miR-142-3p decreased PI3K and p-AKT expression. Up-regulation of NUCKS1 partially reversed the effects of the overexpression of miR-142-3p on the cell viability, cell apoptosis, migration and invasion, as well as PI3K and p-AKT expression in AsPC-1 and MIA-PaCa2 cells. Conclusion: MiR-142-3p regulated the biological characteristics of pancreatic cancer cells by directly targeting NUCKS1.